(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes modern methods of diagnosis of irritable bowel syndrome (IBS) in children. Based on the obtained results, ways of early detection and effective diagnosis of IBS were considered. Modern clinical, laboratory and instrumental diagnostic methods were studied.